A First Taste of MEAD (Measuring Extinction and Abundances of Dust). I. Diffuse Milky Way Interstellar Dust Extinction Features in JWST Infrared Spectra - Marjorie Decleir; Karl D. Gordon; Karl A. Misselt; Burcu Günay; Julia Roman-Duval; Sascha T. Zeegers (The Astronomical Journal)
We present the initial results of the Measuring Extinction and Abundances of Dust project, with a focus on the dust extinction features observed in our JWST near- and mid-infrared spectra of nine diffuse Milky Way sightlines (1.2 ≤ A ( V ) ≤ 2.5). For the first time, we find strong correlations between the 10 μ m silicate feature strength and the column densities of Mg, Fe, and O in dust. This is consistent with the well-established theory that Mg- and Fe-rich silicates are responsible for this feature. We obtain an average stoichiometry of the silicate grains in our sample of Mg:Fe:O = 1.1:1:11.2, constraining the grain composition. We find variations in the feature properties, indicating that different sightlines contain different types of silicates. In the average spectrum of our sample, we tentatively detect features around 3.4 and 6.2 μ m, which are likely caused by aliphatic and aromatic/olefinic hydrocarbons, respectively. If real, to the best of our knowledge, this is the first detection of hydrocarbons in purely diffuse sightlines with A ( V ) ≤ 2.5, confirming the presence of these grains in diffuse environments. We detected a 3 μ m feature toward HD073882 and tentatively in the sample average, likely caused by water ice (or solid-state water trapped on silicate grains). If confirmed, to the best of our knowledge, this is the first detection of ice in purely diffuse sightlines with A ( V ) ≤ 2.5, supporting previous findings that these molecules can exist in the diffuse interstellar medium.